ENGLISH LEARNING PRACTICES - Budiman, Muhammad Arief; Untari, Mei Fita Asri; Listyarini, Ikha (Universitas Pendidikan Ganesha, 2021)
Adequate facilities and infrastructure are not yet ready so that learning cannot run smoothly. The purpose of this study was to analyze the process of learning English. This research is qualitative, descriptive research that tends to use analysis and emphasizes process and meaning more. The approach used in this study is phenomenological. Data collection methods used in this study were interviews, questionnaires, and observation. The instrument used to analyze the data is a questionnaire. The data analysis technique used is descriptive qualitative analysis. The results of this study are that four critical factors support the smooth running of the English learning process: the principal, parents of students, students, and educators. The role of the principal, especially the support of the principal in the form of providing facilities and infrastructure, is an essential factor because, without this learning, it will not be able to run smoothly. The role of parents is also essential because their assistance to students will be able to provide a learning atmosphere. Student motivation is also an essential key to the success of learning English. This research with the results wants to show that various parties pay attention to four main factors for the smooth teaching and learning activities process.